Embodied Carbon in Buildings Measurement, Management, and Mitigation (Springer International Publishing, 2018)
This book provides a single-source reference for whole life embodied impacts of buildings. The comprehensive and persuasive text, written by over 50 invited experts from across the world, offers an indispensable resource both to newcomers and to established practitioners in the field. Ultimately it provides a persuasive argument as to why embodied impacts are an essential aspect of sustainable built environments. The book is divided into four sections: measurement, including a strong emphasis on uncertainty analysis, as well as offering practical case studies of individual buildings and a comparison of materials; management, focusing in particular on the perspective of designers and contractors; mitigation, which identifies some specific design strategies as well as challenges; and finally global approaches, six chapters which describe in authoritative detail the ways in which the different regions of the world are tackling the issue. Provides a comprehensive, up-to-date guide to embodied carbon calculation and reduction, with a particular focus on understanding uncertainty; Includes examples of approaches used by industry professionals, and specific routes to embodied carbon reduction; Identifies the methodologies, tools and standards in use around the world.